Penerapan Standar Operasional Prosedur Oleh Resepsionis Dalam Menangani Tamu Check In dan Check Out di Hotel Cyka Raya Yogyakarta The Implementation of Standard Operating Procedures by Receptionists in Handling Guest Check-In and Check-Out at Hotel Cyka R - Mardiyah, Annisa; Lasally, Adesty; Arifin, Samsul; Welly, Fahry Reva Adiputra (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2024)
A hotel is a building with rooms that are rented out as accommodation or for other commercial needs. Being an industry that operates in the hospitality business service sector, this must be supported by quality service and the existence of infrastructure that can support the implementation of a hotel service business. The purpose of this research is to determine the application of Standard Operating Procedures by receptionists in handling check-in and check-out guests at the Cyka Raya Hotel Yogyakarta. This type of research, the author uses qualitative descriptive with data sources obtained from 20 guests and information from the HRD of the Cyka Raya Hotel Yogykarta. In collecting data, the author used participatory observation, documentation and interviews. Sampling selection method, the author uses quota sampling. For data analysis methods, the author uses data reduction, data presentation, and drawing conclusions and verification. The research results show that the Check-in and Check-Out Standard Operating Procedures (SOP), each of which has 7 indicators, have been implemented quite well, but their implementation is still less consistent due to the lack of Human Resources in several divisions. This means that Standard Operating Procedures do not work well.